Identificação e quantificação de desplacamento cerâmico em fachadas de edifícios no contexto da indústria 4.0 - SOUSA, Alcineide Dutra Pessoa de (Universidade Federal do Pará, 2023)
The facade maintenance process is guided by the results obtained in the inspection phase. Some proposals for methods aimed at improving the inspection process have been discussed, and among these, those that are conducted based on Digital Image Processing (PDI) techniques captured by Unmanned Aerial Vehicle (UAV) stand out. The use of UAVs to capture images on facades streamlines access to the inspected area, and PDI techniques help to automate the process of identifying pathological manifestations. In addition, the fourth industrial revolution has allowed the use of various technological tools in the most varied engineering applications. Among these technologies we can mention cloud computing and computer vision algorithms. In this context, this research aims to apply PDI techniques to detect regions with ceramic displacement on building facades using technologies relevant to industry 4.0 (fourth industrial revolution). The methodological procedure used starts with the formation of a database (images) captured by cell phone and UAV. For modeling purposes, the YOLO (You Only Look Once) object detection algorithm was applied to the images that make up the database using cloud computing. The applied methodology resulted in a program written in python capable of identifying the regions with displacement, quantifying the missing ceramics and exporting the quantification results in a spreadsheet. The identification process had success rates close to 99% and the quantification errors of less than one ceramic per image, which leads to the conclusion of the feasibility of the proposed computational program